Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.1111/ggi.14372
|View full text |Cite
|
Sign up to set email alerts
|

Impact of social engagement on the development of sarcopenia among community‐dwelling older adults: A Kashiwa cohort study

Abstract: How older adults develop sarcopenia in the community setting is unclear. Focusing on social engagement, we aimed to validate our hypothesized model of sarcopenia development with various contributing factors, such as physical activity, oral function, psychological status and nutritional status. We also clarified direct and indirect effects of social engagement, physical activity, nutritional status, oral function and psychological status on new-onset sarcopenia.Methods: We analyzed 1483 participants' (72.6 AE … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 29 publications
0
15
0
Order By: Relevance
“…Previous research has shown that SF status, including low social activity, low social role, and poor social relationships, causes the onset and progression of physical frailty ( 16 ), poor physical performance ( 31 ), and malnutrition ( 32 ), resulting in disabilities ( 14 , 33 , 34 ), and mortality ( 32 , 33 ) in community-dwelling older adults. Close relationships between SF and physical frailty, physical performance, dietary condition, and cognitive function can all exacerbate poor health state and lead to unfavorable consequences.…”
Section: Discussionmentioning
confidence: 99%
“…Previous research has shown that SF status, including low social activity, low social role, and poor social relationships, causes the onset and progression of physical frailty ( 16 ), poor physical performance ( 31 ), and malnutrition ( 32 ), resulting in disabilities ( 14 , 33 , 34 ), and mortality ( 32 , 33 ) in community-dwelling older adults. Close relationships between SF and physical frailty, physical performance, dietary condition, and cognitive function can all exacerbate poor health state and lead to unfavorable consequences.…”
Section: Discussionmentioning
confidence: 99%
“…In previous studies, the Kihon Checklist, which formed the basis of the QMCOO, was reported to be associated with frailty, long‐term care certification and death, being particularly important to this study's results 14–16 . Furthermore, social engagement increases the risk of new certification of long‐term care needs, and decreased social engagement affects various factors and increases the risk of new‐onset sarcopenia 17–19 . Additionally, a decline in oral function, so‐called “oral frailty,” predicts frailty and a new need for long‐term care 20 .…”
Section: Discussionmentioning
confidence: 84%
“…[14][15][16] Furthermore, social engagement increases the risk of new certification of long-term care needs, and decreased social engagement affects various factors and increases the risk of new-onset sarcopenia. [17][18][19] Additionally, a decline in oral function, so-called "oral frailty," predicts frailty and a new need for long-term care. 20 Furthermore, weight loss and low activity are two important phenotypes of frailty, and smoking and dietary intake also have a potentially negative impact on frailty.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, individuals with SO are at greater risk of metabolic disorders and reduced physical performance, such as walking speed, than those with sarcopenia or obesity alone (Sun et al, 2021 ; Tan et al, 2022 ). It was proposed that individuals with SO tended to suffer from impairment of living functions and lower physical capabilities during aging (Hayes and Preacher, 2014 ; Jia et al, 2020 ; Tanaka et al, 2022 ). As a result of lower physical performance, older adults experience difficulties communicating with others and engaging in daily activities (Tolea et al, 2018 ; Tanaka et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…It was proposed that individuals with SO tended to suffer from impairment of living functions and lower physical capabilities during aging (Hayes and Preacher, 2014 ; Jia et al, 2020 ; Tanaka et al, 2022 ). As a result of lower physical performance, older adults experience difficulties communicating with others and engaging in daily activities (Tolea et al, 2018 ; Tanaka et al, 2022 ). Following the social support theoretical model (Wang H. et al, 2019 ), this finding suggests that appropriate late-life social activity may buffer the adverse effects of SO on older adults' cognitive function.…”
Section: Discussionmentioning
confidence: 99%